PENGARUH KMNO4 TERHADAP SIFAT FISIK DAN KANDUNGAN KIMIA SELAMA PEMASAKAN BUAH PISANG AMBON - PANGGABEAN, G.; ROCHAENI, H.; VIVANINGDIAH, I.; CITROREKSOKO, P. (Research Center for Biology-Indonesian Institute of Sciences, 1987)
G. PANGGABEAN, H. ROCHAENI, I. VIVANINGDIAH & P. CITROREKSOKO. 1987. The effect of KM11O4 on physical and chemical consituents during the ripening of